Effects of post-bleeding vascular infusion of cattle with a solution of sugars, sodium chloride, and phosphates with or without vitamin c on carcass traits, Warner-Bratzler shear forces, and patalability - Yancey, E.J.; Dobbels, T.E.; Katasanidis, E.; Dikeman, Michael E.; Chambers, Edgar, IV (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two groups of grain-finished, crossbred Charolais steers were utilized to determine the effects of post-bleeding vascular infusion on dressing percentages, USDA quality and yield grades, Warner-Bratzler shear force values, and flavor. Nine steers from one group of 18 were infused with a solution containing sugars, sodium chloride, and a phosphate blend (MPSC), and the remaining nine steers served as noninfused controls. Nine in the second slaughter group of 18 were MPSC-infused, and nine were infused with the MPSC solution plus 500 ppm vitamin C (MPSC+C). The MPSC cattle had a 2.9% higher mean dressing percentage (P<.05) than control cattle. Vascular infusion had no effect (P>.05) on Warner-Bratzler shear force or USDA quality and yield grades. Results from a descriptive flavor profile sensory panel showed some significant differences in flavor profile characteristics, but these differences were small and inconsistent. Vascular infusion with MPSC or MPSC+C increased carcass weights, had few effects on USDA quality or yield grades or shear force, and had no consistent effects on flavor profile characteristics of cooked beef.
Keywords: Beef; Vascular infusion; Flavor profile analysis